Inferioritas Tokoh dalam Novel Prasetyane Wanita Karya Tulus Setiyadi: Kajian Psikologi Individual Alfred Adler - Lailiyatul Fauziyah; Octo Dendy Andriyanto (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Inferiority is a feeling that arises in a person, characterized by feelings of weakness and being lower than others due to certain imperfect circumstances in social life. A person with low social interest and an abnormal lifestyle often experiences feelings of inferiority or low self-esteem. The author examines the personalities of characters experiencing inferiority in the novel Prasetyane Wanita by Tulus Setiyadi, published in 2020. The objectives of this study are (1) to explain the manifestations of the characters' inferiority. This research is a qualitative study using a descriptive qualitative method to describe the manifestations of inferiority with the aim of understanding the psychological meanings of the characters. The literary psychology theory used is Alfred Adler's individual psychology theory, which aligns with the research on the inferiority feelings experienced by individuals and the efforts they make to become superior. The data source for this research is the novel